2021
DOI: 10.1136/bmjopen-2020-041553
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital triage of patients with acute cardiac complaints: study protocol of HART-c, a multicentre prospective study

Abstract: IntroductionEmergency department (ED) overcrowding is a major healthcare problem associated with worse patient outcomes and increased costs. Attempts to reduce ED overcrowding of patients with cardiac complaints have so far focused on in-hospital triage and rapid risk stratification of patients with chest pain at the ED. The Hollands-Midden Acute Regional Triage—Cardiology (HART-c) study aimed to assess the amount of patients left at home in usual ambulance care as compared with the new prehospital triage meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Ambulance nurses and GPs can perform this prehospital triage and leave patients at home when ED referral is not necessary, as was done for cardiac complaints in the HART-c study. 24 When increasing the number of beds and improving prehospital triage offered insufficient solace, collaboration with neighboring hospitals is a next step. The Modena Taskforce response in Italy implemented a dashboard called Pagoda to show the number of positive tests and ICU occupancy throughout the region.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulance nurses and GPs can perform this prehospital triage and leave patients at home when ED referral is not necessary, as was done for cardiac complaints in the HART-c study. 24 When increasing the number of beds and improving prehospital triage offered insufficient solace, collaboration with neighboring hospitals is a next step. The Modena Taskforce response in Italy implemented a dashboard called Pagoda to show the number of positive tests and ICU occupancy throughout the region.…”
Section: Discussionmentioning
confidence: 99%
“…23 After conducting patients' medical condition and history assessment, physical examination with vital sign monitoring, and other diagnostic procedures, EMS paramedics can either tele-transmit the result to a physician and get notified with text or audio for further advice for diagnosis or therapy 24 , or use audio and video features where they can connect virtually to physicians. [16][17][18][19]22,24,25,27 Catapan et al 33 found that video teleconsultation has numerous benefits. A few of the benefits are the ability to diagnose accurately, similar to face-to-face, the ability to deliver care without moving the patient, and the ability to adapt to current time constraints for health care.…”
Section: Discussionmentioning
confidence: 99%
“…A monitor or defibrillator monitor can be used to tele-transmit ECG from ambulances for interpretation by a physician. 16,20 The advantage of using a monitor that can tele-transmit ECG is that if there is any new change in the ECG, consultation or treatment for this condition can be started immediately. 20 Another advanced pre-hospital technology is the Mobile Stroke Unit (MSU) for stroke-suspected emergency patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 It is well known that this is associated with shorter ischaemic times and subsequent improved clinical outcomes. [9][10][11] On the other hand, the use of additional diagnostic tools could help to definitively rule out an NSTE-ACS in the prehospital setting in chest pain patients with a low suspicion for NSTE-ACS. This is important as only 11%-21% of these patients presenting to an emergency department are finally diagnosed with an NSTE-ACS, in the remaining majority generally no life-threatening condition is found.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%